Defect reversibility regulates dynamic tensile strength in silicon carbide at high strain rates. (May 2022) - Li, Wanghui; Hahn, Eric N.; Branicio, Paulo S.; Yao, Xiaohu; Germann, Timothy C.; Feng, Biao; Zhang, Xiaoqing
Abstract: To reveal the relationship between atomic-scale activity and bulk materials properties, we report all-atom molecular dynamics (MD) simulations of the deformation and dynamic failure of mono- and nanocrystalline silicon carbide (SiC) ceramics. We establish a direct link between the reversibility of defects and dynamic tensile strength of a nominally brittle ceramic over a wide range (six orders of magnitude) of strain rates, bridging the simulation regime to current experimental capabilities that enable the observation of lattice dynamics over extremely short timescales. Our results reveal that SiC exhibits a highly reversible deformation twinning mechanism in response to loading along the [001] crystal direction below a critical compression strain. The remarkable reversibility of the active defects allows the crystal to retain its high strength. Beyond a critical strain, the process becomes unstable, and self-activated twin boundary motion is triggered, yielding irreversibly intertwined defects, resulting in a significant reduction in strength. Graphical abstract: Image, graphical abstract